Numerical studies of nonlinear gearing models using bond graph method - Margielewicz, Jerzy; Wojnarowski, Józef; Zawiślak, Stanisław (Zielona Góra: Uniwersytet Zielonogórski)
The present paper is dedicated to computer simulations performed using a numerical model of a one-stage gear. The motion equations were derived utilizing the bond graph method. The formulated model takes into consideration the variable stiffness of toothings as well as an inter-tooth clearance which has been represented via discontinuous elements with so called dead zones. As a result of these assumptions, the nonlinear model was obtained which enables representation of the dynamic phenomena of the considered gear.
Keywords: chaos; nonlinear vibrations; Lapunov exponent; bifurcations